2014
DOI: 10.1063/1.4867522
|View full text |Cite
|
Sign up to set email alerts
|

Detection and localization of a defect in a reverberant plate using acoustic field correlation

Abstract: Green's function can be retrieved from cross-correlation of a diffuse field generated by noise sources. Today, this important result is the fundamental of several passive imaging techniques. The aim of this paper is to establish the suitability of these methods to detect and locate a defect in a reverberant elastic plate. The relations between the noise cross-correlation function over a few number of noise sources and the imaginary part of the Green's function are derived and numerically validated. Then we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 22 publications
1
41
0
Order By: Relevance
“…Theoretical and experimental studies in several areas [16]- [21], have shown the existence of a relationship between the Green's function (acoustic impulse response) between two measurement points and the cross-correlation of noise signals recorded at these points.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical and experimental studies in several areas [16]- [21], have shown the existence of a relationship between the Green's function (acoustic impulse response) between two measurement points and the cross-correlation of noise signals recorded at these points.…”
Section: Methodsmentioning
confidence: 99%
“…original ultrasound technique relying on the correlation of non-coherent acoustic fields [13] [14] [15] [16]. Based on passive Green's function reconstruction [17], the principle is that such fields, ordinarily considered as noise in conventional NDT applications, can be judiciously exploited to estimate the response between two measurement points without the need for an active ultrasound source at one of these points.…”
Section: Recent Theoretical and Experimental Work Have Demonstrated mentioning
confidence: 99%
“…Theoretical and experimental studies in several areas [25][26][27][28], have shown that the active acoustic signal between two measurement points can be passively estimated from the time derivative of the correlation function of the signal recorded at those points.…”
Section: Passive Detection Methodsmentioning
confidence: 99%
“…Equation (2.3) shows that the Green's function associated with two locations r R l and r R l where sensors are deployed can be reconstructed by cross-correlation of the ambient recordings made by the two sensors, provided that the ambient noise is diffuse [26].…”
Section: Interferometry With Lamb Wavesmentioning
confidence: 99%
“…According to [26], the cross-correlation is related to the imaginary part of the Green's function by…”
Section: Interferometry With Lamb Wavesmentioning
confidence: 99%